DESCRIPTION OF HEMOGLOBIN LEVELS IN PRE AND POST-OPERATING PATIENTS IN RSUD TOTO KABILA, BONE BOLANGO DISTRICT - Ainun Miftahul Zannah Biya (Jurnal Ilmiah dr. Aloei Saboe, 2022)
Hemoglobin (Hb) is a protein found in erythrocytes which acts as a marker of anemia. Anemia is a health problem in all over the world, especially in developing countries, it is estimated that 30% of the world's population suffer from anemia. One of the causes is bleeding, which is a condition of losing large amounts of blood. Surgery is an action by medical professionals performed to save a patient's life. However, during the operation there is also a risk of bleeding which can affect hemoglobin levels. This study aims to determine the description of hemoglobin (Hb) levels in pre and postoperative patients. This type of research is quantitative descriptive with purposive sampling technique of sampling of 33 respondents divided based on pre-operation and post-operation. The results of the examination found that all preoperative respondents had moderate anemia with a percentage of 12.1%, (4 respondents), mild anemia with a percentage of 21.2% (7 respondents), very mild anemia with a percentage of 9.1% (3 respondents), with normal hemoglobin levels, namely 69.7% (23 respondents). and for postoperative respondents who had mild anemia with a percentage of 15.2%, (5 respondents), very mild anemia with a percentage of 21.2%, (7 respondents) with normal hemoglobin levels of 51.5% (17 respondents). The need for this research to be further developed regarding the description of pre and postoperative hemoglobin levels by using the characteristics of respondents based on age.